Endoscopic Third Ventriculostomy: Preoperative Considerations and Intraoperative Strategy Based on 300 Procedures - Di Vincenzo, Jana; Keiner, Doerthe; Gaab, Michael R.; Schroeder, Henry W. S.; Oertel, Joachim M. K. (Journal of Neurological Surgery Part A: Central European Neurosurgery, 2014)
Purpose Although successful endoscopic third ventriculostomy (ETV) has been reported for many indications, peculiarities of the surgical technique in each separate indication require particular respect.Methods A detailed account of the authors' surgical technique, their presurgical considerations, and their intraoperative strategies to perform ETV is presented. Surgery of representative obstructive hydrocephalus cases in posterior fossa lesions (cerebellar infarction, posterior fossa tumor), in distortion of the ventricular system (intracranial hemorrhage, basilar artery aneurysm) and in membranous obstruction (aqueductal stenosis, posterior fossa malformation), is illustrated in detail.Results In posterior fossa lesions, careful evaluation of the prepontine space and localization of the basilar artery is mandatory. Recognition of mammillary bodies and infundibular recess is of particular importance since the third ventricle floor is rather thick and nontranslucent. In distortion of the ventricular system, careful analysis of the preoperative imaging allows the selection of the optimal approach. Sometimes, blood clot removal and vigorous irrigation is required. Frequently, the landmarks are difficult to identify. These are cases for experienced endoscopic neurosurgeons. In aqueductal stenosis and posterior fossa malformation, perforation of the often thin and translucent ventricular floor is easy because of clear anatomical landmarks. Those are ideal candidates for ETV. For experienced neuroendoscopists, the authors advocate inspection of the fourth ventricle with a flexible scope to ensure cerebrospinal fluid (CSF) circulation obstruction.Conclusions ETV is a frequent and well-established endoscopic technique. Based on the underlying pathology, the technique has to be modified to obtain good results with minimal complications.
Keywords: endoscopic third ventriculostomy; endoscopic surgical techniques; obstructive hydrocephalus